2014
DOI: 10.1097/aog.0000000000000184
|View full text |Cite
|
Sign up to set email alerts
|

Change in Sexual Behavior With Provision of No-Cost Contraception

Abstract: Objective To estimate whether providing no-cost contraception is associated with the number of sexual partners and frequency of intercourse over time. Methods This was an analysis of the Contraceptive CHOICE Project, a prospective cohort study of 9,256 adolescents and women at risk for unintended pregnancy. Participants were provided reversible contraception of their choice at no cost and followed with telephone interviews at 6 and 12 months. We examined the number of male sexual partners and coital frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 13 publications
0
18
0
4
Order By: Relevance
“…We found that 71% of study participants reported no change in the number of sexual partners at 12 months compared with baseline, and only 16% reported an increase. 17 Of those reporting an increase in sexual partners, more than 80% reported a change from zero partners to one partner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that 71% of study participants reported no change in the number of sexual partners at 12 months compared with baseline, and only 16% reported an increase. 17 Of those reporting an increase in sexual partners, more than 80% reported a change from zero partners to one partner.…”
Section: Resultsmentioning
confidence: 99%
“…21 In addition, we did not find an increase in risky sexual behavior or more STIs with increased LARC use. 17 Thus, increased utilization of LARC methods is an important strategy to reduce unintended pregnancies, which would both improve women's health and save health care dollars. 22 The CHOICE Project provided a model of contraceptive provision that was unique but adaptable.…”
Section: Discussionmentioning
confidence: 99%
“…Urodynamics were not obligatory because there is no evidence that urodynamics will improve treatment outcome, and it could only hinder inclusion in the study. 2,3 Jha showed that prolapse surgery was altered by the results of urodynamics investigation in just 7% of cases. 4 In conclusion, we are confident that the study is a good reflection of daily practice.…”
Section: Referencesmentioning
confidence: 99%
“…3 Even if it did not affect young women's decisions, knowing that girls are routinely made infertile may well affect the behaviour of men. Coercion of young women at first sex is higher the younger the age at first sex, and the majority of those who report first sex before age 16 regret the timing.…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation